Three approaches to evaluate of the heat dissipated during fatigue crack propagation experiments (Fracture and Structural Integrity, 2019)
This work is devoted to the comparative analysis of three techniques for measurement of energy dissipation in metals under fatigue crack propagation: original contact heat flux sensor, post-processing of the infrared thermography data and lock-in thermography. The contact heat flux sensor allows real-time recording of the heat source value. Non-contact temperature measurements by infrared thermography techniques allows one to calculate the heat source field on the specimen surface using the solution of heat conductivity equation. Lock-in thermography is a well-established technique for measuring of the dissipated energy under cyclic loading based on the analysis of the second harmonic amplitude of the thermal signal. This paper deals with the V-notched flat specimens made of stainless steel AISE 304 subjected to cyclic loading. It was shown that the dissipated energy values estimated by different techniques have a good qualitative agreement. Contact and non-contact measurements can be used for investigation on energy dissipation either in combination or separately. The measured values allows one to propose a relation between the fatigue crack growth rate and dissipated heat near the crack tip.
Keywords: IR-thermography; Lock-in thermography; Heat flux sensor; Dissipated energy; Fatigue crack propagation